Legal Uncertainty in Law Enforcement for Drug Addicts Resulting in Criminal Disparity - Winjaya Laksana, Andri; Budi Susilo, Adhi; Rinda Listyawati, Peni; Widiyoko, Setiawan; Triyanto, Toni (Universitas Airlangga, 2025)
The application of Articles in law enforcement against drug addicts that should be imposed on dealers, dealers or couriers, but instead imposed on addicts, causes legal uncertainty for addicts because the rights of addicts to be rehabilitated are not obtained. This paper uses normative legal research methods. The research approach used is a statutory approach and a case study approach. The results of this study are legal uncertainty in law enforcement against drug addicts in Indonesia, which is caused by multiple interpretations between Article 127 and Article 112 of Law Number 35 of 2009 concerning Narcotics, which has created disparities in sentencing that ignore the principle of justice. The use of Article 112 which should be intended for drug dealers is often misused to ensnare addicts, who should receive rehabilitation according to Article 127. The need for legal reconstruction that focuses on harmonizing Article 127 and Article 112 of the Narcotics Law to align the two articles, by providing quantitative limitations and clear criteria to distinguish abusers from dealers.